2014
DOI: 10.3390/ijms151017380
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia Induces Apoptosis through Endoplasmic Reticulum and Reactive Oxygen Species in Human Osteosarcoma Cells

Abstract: Osteosarcoma (OS) is a relatively rare form of cancer, but OS is the most commonly diagnosed bone cancer in children and adolescents. Chemotherapy has side effects and induces drug resistance in OS. Since an effective adjuvant therapy was insufficient for treating OS, researching novel and adequate remedies is critical. Hyperthermia can induce cell death in various cancer cells, and thus, in this study, we investigated the anticancer method of hyperthermia in human OS (U-2 OS) cells. Treatment at 43 °C for 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 39 publications
4
60
1
1
Order By: Relevance
“…A large number of studies have reported that hyperthermia reduces cell viability mainly through a mechanism that involves induction of apoptosis . The results presented herein demonstrate that melatonin potentiates the apoptotic response in U937 cells exposed to hyperthermia.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…A large number of studies have reported that hyperthermia reduces cell viability mainly through a mechanism that involves induction of apoptosis . The results presented herein demonstrate that melatonin potentiates the apoptotic response in U937 cells exposed to hyperthermia.…”
Section: Discussionsupporting
confidence: 51%
“…A large number of studies have reported that hyperthermia reduces cell viability mainly through a mechanism that involves induction of apoptosis. 27,53,54 The results presented herein demonstrate that melatonin potentiates the apoptotic response in U937 cells exposed to hyperthermia. In most experiments performed in this study, melatonin was added to cell culture 1 hour before starting hyperthermia; differences in the apoptotic rate were not appreciated with longer preincubation times (3 hours) as well as when the indoleamine was added just at the beginning of heat treatment (data not shown).…”
Section: Discussionmentioning
confidence: 58%
“…After heat exposure without trabectedin (41.8 or 43°C), however, we found no significant induction of apoptosis or senescence in SW872 and U2OS. In contrast, hyperthermia alone was shown to induce apoptosis in U2OS beginning at 43°C with remarkably greater amounts of apoptotic cells after temperatures of 45°C and higher . Different heat doses applied or other methodical differences can explain why we detected nearly no induction of apoptosis at 43°C.…”
Section: Discussioncontrasting
confidence: 55%
“…In conclusion, hyperthermia induced cell apoptosis substantially via the ROS, ER stress, mitochondria, and caspase pathways (Hou et al 2014). In addition, Yoo et al (2012), demonstrated that ROS-generating magnetic nanoparticles can effectively sensitize cancer cells to make them highly vulnerable to subsequent apoptotic magnetic hyperthermia at low temperatures (43°C).…”
Section: Ptt Triggers Oxidative Stressmentioning
confidence: 99%